Novel MLL/KMT2A‐MON2 fusion in a child with therapy‐related acute myeloid leukemia after treatment for acute promyelocytic leukemia. Issue 11 (8th July 2021) - Gong, Yanlei; Wang, Man; Shen, Hongjie; Chen, Yan; Cen, Jiannong; Yin, Xiaolin; Yao, Li
Abstract: Acute promyelocytic leukemia (APL) is a distinct subtype of acute myeloid leukemia (AML), which is characterized by the reciprocal t (15;17) (q24; q21) translocation, resulting in PML–RARA gene fusion. Therapy‐related AML (t‐AML) is a serious complication after cytotoxic and/or radiation therapy in many malignant diseases. In this report, MLL/KMT2A‐MON2, with balanced chromosomal translocation t (11;12) (q23; q14), was identified as a novel fusion in a child transformed to t‐AML after successful treatment of APL. This study emphasized that clinical monitoring with an integrated laboratory approach is essential for the diagnosis and treatment of t‐AML.